IDENTIFIKASI DAN PENILAIAN RISIKO KERJA MENGGUNAKAN METODE SWIFT PADA BENGKEL OTOMOTIF SKALA MENENGAH STUDI KASUS: CV XYZ - Fitra, Fitra; Susanti, Lusi; Zadry, Hilma Raimona; Hafrida, Elisa; Mawadah, Dinar; Anggraini, Dewi (Universitas Putera Batam, 2025)
Workplace accidents remain a significant concern in small and medium enterprises (SMEs), particularly in sectors with high physical labor intensity such as automotive repair workshops. This study aims to identify and assess occupational hazards in CV XYZ, a medium-sized workshop specializing in engine and body repair, using the Structured What-If Technique (SWIFT). Through field observations, interviews, and questionnaires, data were collected on potential hazards during major work processes. The SWIFT method was applied to examine risks based on frequency and severity, culminating in a Risk Rating Number (RRN) for each hazard. The study found 23 hazards in engine repair activities and 20 in body repair, with six identified as top-priority risks (RRN = 10). These included crush injuries, lacerations, and unsafe working postures. Recommendations were proposed to reduce risk levels, including the use of ergonomic tools, implementation of personal protective equipment (PPE), safety training, and workplace layout improvements. The findings underscore the effectiveness of the SWIFT method in fostering participatory risk assessment and enhancing safety awareness in SMEs. This approach provides a practical model for similar workshops aiming to improve their occupational safety and health (OSH) performance systematically.